Implementation of Online Learning Strategies Based on Student Grit at Charis Christian Elementary School - Susane Ikawati (CV. Edutechnium Indonesia, 2025)
The Covid-19 pandemic has changed education in the world and especially in Indonesia, every school must begin to adjust to be able to continue to provide quality distance learning. Charis Christian Elementary School has been using online learning strategies since the first day distance learning was implemented in Indonesia. Student grit is one of the important factors for students to be able to successfully undergo online learning. Grit is a combination of passion, resilience, determination, and focus that will encourage a person to be disciplined and optimistic in pursuing what he is doing even though he has to face discomfort, rejection, and progress that is not too significant. The results of the pretest using the Grit Scale get an average result of 36.2 with a total of 30 students (N = 30) respondents, while the posttest results get an average (mean) = 39.56. Success in online learning requires students to demonstrate self-regulation, discipline, fortitude, toughness, and all the attributes that describe grit. Through this research, it is hoped that it can inspire and encourage the development of grit-based learning that will enable students to achieve success in running online learning.